PESAN KOMUNIKASI PENDIDIKAN DI MEDIA TELEVISI - Dewi K. Soedarsono (Program Studi Ilmu Komunikasi FBIK Unissula, 2012)
The growth of Communication and information technology information in Indonesian with many more of Television medium, and so make various of broadcasting program that consump- tion for Indonesian people . TheÂ various program has been reason many produsen make compe- tition program who can be audience interest . The ï€‚ are up physical and verbal violence in many Indonesian area , that implication from Television program as news, sinetron or ï€ lm has been showing of audience with continued . The phenomenal of condition medium audience , then educationÂ communication role has very important done to produsen with Laswell approach as a basic mass communication activity and Kode Etik Penyiaran function as to received education message for every audience . TheÂ foundation of Laswell conception who that to come of mass medium potential like Television as one of communication education medium , we hope all everyone that concern activity on mass medium , with together and mutual support to create of program who can be education as simultance on all human life and the future has to create of condition that safety andÂ confortable for Indonesian people.